Pola Asuh Ibu Berbasis Family Center Nursing dalam Meningkatkan Status Nutrisi pada Balita dengan Stunting - Mansur, Rumzil Laila; Hidayat, Syaifurrahman; Wahid, Abd. (Fakultas Ilmu Kesehatan, 2024)
Inadequate or poor parenting can also cause growth retardation. Parents and mothers must understand the amount of nutrition that must be given to children, including food and environmental hygiene, as well as the use of appropriate health facilities to deal with children's problems, especially those related to child nutrition. The design used is qualitative with a phenomenological approach. The sampling technique used was purposive sampling which was carried out in the Saronggi Health Center Work Area located in Nambakor Village, Saronggi District in February 2024 with a total of 7 participants, 6 main participants and 1 key participant. The data collection technique uses in-depth interview techniques, the data analysis carried out is thematic analysis. This research answers the parenting style based on Family Center Nursing in improving the nutritional status of toddlers with stunting. Nutrition for toddlers with stunting has not been fulfilled even though the mother feels that she is providing adequate nutrition for toddlers. Socio-Cultural Aspects; Providing food according to nutritional needs, managing rest schedules, and maintaining personal hygiene for stunted toddlers, while serving meals in a varied menu. Developmental Stages; Mothers feed toddlers by engaging them in activities such as walking around and playing with their peers while offering food. Environmental Factors; Washing food ingredients thoroughly before cooking or serving. Washing hands with soap every time before feeding the child. Family Structure; Families make decisions regarding the care and upbringing of toddlers, playing a vital role in ensuring adequate nutritional intake for young children. Socialization Process; Mothers actively involve their children in monthly. In this research there are 6 themes, namely: socio-cultural, history of family development, environment, family structure, stress coping and family adaptation.